2012
DOI: 10.1186/1471-2393-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Revising acute care systems and processes to improve breastfeeding and maternal postnatal health: a pre and post intervention study in one English maternity unit

Abstract: BackgroundMost women in the UK give birth in a hospital labour ward, following which they are transferred to a postnatal ward and discharged home within 24 to 48 hours of the birth. Despite policy and guideline recommendations to support planned, effective postnatal care, national surveys of women’s views of maternity care have consistently found in-patient postnatal care, including support for breastfeeding, is poorly rated.MethodsUsing a Continuous Quality Improvement approach, routine antenatal, intrapartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Of these studies, two were RCTs,32 40 one was a non-randomised controlled study,36 a further study was a before–after intervention study,19 and another three33 37 41 were cohort studies. The remaining 27 studies were cross-sectional surveys, 20 of which were national surveys with sample sizes ranging from 113734 to 26 325 30.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, two were RCTs,32 40 one was a non-randomised controlled study,36 a further study was a before–after intervention study,19 and another three33 37 41 were cohort studies. The remaining 27 studies were cross-sectional surveys, 20 of which were national surveys with sample sizes ranging from 113734 to 26 325 30.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous CQI research in pregnancy care has been hospital-based, implemented in a single service, not focused on metabolic screening, or not conducted in Australia. [23][24][25] Our research applied a unique systemwide participatory approach to assess systemic issues commonly affecting provision of care. 14 It used a detailed, longitudinal dataset to investigate long-term sustainability, and included many PHCs across several settings.…”
Section: E5mentioning
confidence: 99%
“…Another speculative assumption is that midwives, who delivered the majority of parous women, have less knowledge in perineal anatomy and therefore tend to miss OASIS more than doctors. 31 Zimmo et al 17 described that after the expert workshop 54% midwives reported good knowledge of perineal anatomy compared with 79% doctors. This may also justify the higher OASIS rates observed in births attended by doctors.…”
Section: Discussionmentioning
confidence: 99%